Loading

Since the equation for y is given in the format y=u/v, the use of the quotient rule is the easiest way to find the differential of this equation. The quotient rule states, (vu'-uv')/v^2 is equal to the differential of u/vIn this situation u=3x+1 and v=2x+1. The first step to take would be to differentiate the individual parts of the equation so, u'=3 and v'=2.These 4 values can then be put into the quotient rule in order to reach the result of the differential. dy/dx=(3(2x+1)-2(3x+1))/(2x+1)^2, which can be simplified down to dy/dx=1/(2x+1)^2